Calculo Situacional a Estrategia Em Quaisquer Circunstancias (Global Journal of Human-Social Science, 2021)
This work addresses the ability of an agent to not have to adapt to change but rather force others to adapt by manipulating the environment This implies ability to influence others and ability to ignore their interests and actions To this end in selected aspects the Situational Strategic Planning PES as formulated by Carlos Matus in his book Goodbye Mr President MATUS 1996 with teachings by Miyamoto Musashi in the work Gorin No Sho MUSASHI 1992 Epistemologically the work is conducted by the vision underlying the evolution of the concept approached as object As a method of investigation the bibliographical research of seminal works was privileged The text is structured in four sections The Presentation raises the question to be addressed in the article the methodology and the limits and expectations of results The Introduction places the reader on the object to be addressed in the main section The following section Calculation and Interactive Situation constitutes the development of the argumentation and precedes the Final Considerations that closes the exposure of the proposed reasoning The bibliographic references close the work
Keywords: situational strategic planning; strategy; circumstances; situation